To study the prevalence and types of nutritional anemia in under-five children with severe acute malnutrition - Jangid, Roshan Kumar; Kumar, Arun; -, Anita; Mahapatra, Chinmaya; Yadav, Manoj; Singhal, Sidhant; Laxminarayan, Kartik (Indian Journal of Child Health, 2020)
Background: Anemia is an important comorbidity in under-five children with severe acute malnutrition (SAM). The data on evaluation of SAM are limited. Aim: This study was done for analysis of incidence and types of anemia prevalent in SAM children. Materials and Methods: It was a hospital-based prospective observational study conducted from July 2017 to December 2018. A total of 260 children of age